The role of fine-needle aspiration biopsy (FNAB) in the diagnostic management of parotid gland masses with emphasis on potential pitfalls - Dostalova, Lucie; Kalfert, David; Jechova, Alzbeta; Koucky, Vladimir; Novak, Stepan; Kuchar, Martin; Zabrodsky, Michal; Novakova Kodetova, Daniela; Ludvikova, Marie; Kholova, Ivana; Plzak, Jan (European archives of oto-rhino-laryngology, 2020)
PURPOSE: The treatment strategy of parotid gland tumours depends mainly on the histopathological type of the lesion. Fine-needle aspiration biopsy (FNAB) is recommended in preoperative diagnostics. The aim of the study was to evaluate the FNAB standing in the diagnostic algorithm of parotid gland lesions and to correlate FNAB results in relation to the definitive histopathological diagnosis. MATERIAL AND METHODS: The retrospective analyses of 651 examined and consequently surgically treated parotid gland lesions at the Department of Otorhinolaryngology and Head and Neck Surgery, 1st Faculty of Medicine, Charles University in Prague between 2006 and 2016 were used. Preoperative cytological results were consequently evaluated in relation to the definitive histopathological diagnosis. RESULTS: The cohort consisted of 367 women and 284 men (average age 58 years). FNAB was diagnostic in 604 (92.8%) patients and non-diagnostic in 47 (7.2%) patients. The result of FNAB was positive (suspicious for malignant tumour) in 89 (14.7%) patients and negative (benign) in 515 (85.3%) patients. Sensitivity of the examination was 80.00%, specificity was 93.82%, PPV 62.92%, NPV 97.28%, and LR + and LR- were 12.95 and 0.21, respectively, with an accuracy of 92.22%. CONCLUSION: Our results confirm the significant role of FNAB in the diagnostic algorithm of parotid gland lesions.
Keywords: Retrospective Studies; Parotid Gland; Middle Aged; Biopsy, Fine-Needle; mužské pohlaví; Sensitivity and Specificity; parotis; Parotid Neoplasms; ženské pohlaví; tenkojehlová biopsie; retrospektivní studie; Humans; Parotid gland; nádory příušní žlázy; lidé středního věku; senzitivita a specificita; Salivary gland; Female; Tumour; FNAB; lidé; Male